STRATEGI LEMBAGA DAKWAH KAMPUS AL-JAMI’ DALAM MEMBENTUK PEMAHAMAN AGAMA DI KALANGAN MAHASISWA - Syahru Ramadhan (Fakultas Dakwah dan Komunikasi, 2020)
This paper discusses the al-Jami Campus Da'wah Institute strategy in shaping religious understanding among students, al-Jami Campus Da'wah Institute is the first intra-campus institution in the UIN Alauddin Makassar environment, as the central preaching in the campus environment until now, as for the objectives the establishment of this institution as a means to instill understanding of Islam in the form of the values of faith, worship and morals among students, over time the Campus Preaching Institutions that exist on campus have emerged, so that the existence of LDK al-Jami sometimes does not have an existence as a missionary institution on campus in preaching because of the many preaching institutions that have sprung up, both in the name of intra and extra-campus institutions, the preaching strategy undertaken by the campus missionary institution by using several patterns so that it can attract students to join and conduct ongoing coaching through mentors ing, general studies, and special studies. This paper tries to examine the pattern of coaching conducted by LDK al-Jami in preaching in the UIN Alauddin Makassar environment.